Comparison of Effectiveness of Mindfulness and Happiness Training in Promoting Parent-Child Interaction Case Study: Mothers of Anxious Preschool Children in Shahrekord city, Southwest of Iran, 2018 - Arjang Fereydooni; Alireza Heidari; Zahra Eftekhar Saadi; Parvin Ehteshamzadeh; Reza Pasha (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Anxiety disorders are common psychiatric disorders in children and adolescents.  It seems that the parent-child interaction affects or exacerbates the creation of anxiety disorders in children. The present study aimed to compare the effectiveness of mindfulness and happiness training in promoting parent-child interaction in mothers of anxious preschool children. Methods: The research method was experimental with a pretest-posttest design and control group. The statistical population included all mothers of pre-school anxious children in Shahrekord in 2018. Using the multistage sampling method, 45 people were selected and put randomly in the control and two experimental groups (n=15 per group). The Spence Children's Anxiety Scale (SCAS) and Pianta's Child-Parent Interaction Questionnaire (PACHIQ) were used for data collection. Experimental groups were put under mindfulness (eight 90-minute sessions) and happiness (ten 90-minute sessions) training, but the control group did not receive any intervention. Analysis of the data involved both inferential and descriptive statistics including mean, standard deviation. Data analysis was conducted using one-way analysis of variance (one-way ANOVA) and analysis of covariance (ANCOVA). SPSS version 24 was further used for analyzing the data. The significance level of research was considered to be α=0.05. Results: The results indicated that both mindfulness (p=0.0001) and happiness (p=0.0001) training increased parent-child interaction in mothers of anxious preschool children. The mean ± SD of the post-test score of parent-child interaction in the control group was 96.73±7.89 which was significantly different from the experimental groups (p=0.0001). Furthermore, there was no significant difference between the effectiveness of mindfulness (117.80±4.47) and happiness training (115.46±4.65) in promoting parent-child interaction in mothers of anxious children (p=0.599). Conclusion: Mindfulness and happiness training were effective in improving parent-child interaction in mothers of preschoolers with anxiety and could similarly change the parent-child interaction in mothers of anxious children.